2022
DOI: 10.1126/sciadv.abl3888
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically reinforced biotubes for arterial replacement and arteriovenous grafting inspired by architectural engineering

Abstract: There is a lack in clinically-suitable vascular grafts. Biotubes, prepared using in vivo tissue engineering, show potential for vascular regeneration. However, their mechanical strength is typically poor. Inspired by architectural design of steel fiber reinforcement of concrete for tunnel construction, poly(ε-caprolactone) (PCL) fiber skeletons (PSs) were fabricated by melt-spinning and heat treatment. The PSs were subcutaneously embedded to induce the assembly of host cells and extracellular matrix to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 59 publications
(116 reference statements)
1
38
0
Order By: Relevance
“…Immunofluorescence staining revealed that the lumen surface of rat-derived PBs (inner diameter: 2 mm) and canine-derived PBs (inner diameter: 3.5 mm) were covered by α-smooth muscle actin-positive (α-SMA + ) cells ( Figs. S1e and f , Supporting Information), which was in-line with our previous observations [ 51 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Immunofluorescence staining revealed that the lumen surface of rat-derived PBs (inner diameter: 2 mm) and canine-derived PBs (inner diameter: 3.5 mm) were covered by α-smooth muscle actin-positive (α-SMA + ) cells ( Figs. S1e and f , Supporting Information), which was in-line with our previous observations [ 51 ].…”
Section: Resultssupporting
confidence: 92%
“…Subcutaneous implantation of our previously optimized melt spun PCL fiber skeleton [ 51 ] was re-employed in this study to generate PBs. Firstly, the optimized melt-spin preparation parameters were followed, and the resultant PCL fiber skeletons were morphologically characterized ( Table S1 and Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This demonstrated that using macro‐porous vascular grafts improved the regeneration of the neo‐vessel which mirror the structure and function of the native arteries. More recently, Zhi et al (2022) created PCL‐based vascular grafts inspired by architectural engineering. Specifically modeled after architectural design of steel fiber reinforcement of concrete for tunnel construction, PCL fiber skeletons were fabricated by melt‐spinning and heat treatment before subcutaneous embedding for the deposition of cells and ECM.…”
Section: Bioengineering Strategies To Combat Vascular Graft Calcifica...mentioning
confidence: 99%